Developing Fuzzy Inference System of the Observed Albireo Star’s Trail using Surface Meteorological Parameter over ITERA Astronomical Observatory (IAO) - Wahyu Sasongko Putro; Wirid Birastri; Robiatul Muztaba; Anissa Novia Indra Putri; Nindhita Pratiwi; Hakim Luthfi Malasan (Universitas Ahmad Dahlan, 2018)
This study aims to develop Fuzzy Inference System (FIS) trail of star seeing over ITERA Astronomical Observatory (IAO) using surface meteorological parameter during site selection to develop observatory. The one-day surface meteorological observation such as Pressure (P), Temperature (T), and Humidity (H) and trail of Albireo (β Cyg) star seeing value was taken from Mt. Betung, Lampung, Indonesia. The surface meteorological data are analyzed to obtain Albireo (β Cyg) star seeing value in 3 to 4 August 2017. By using statistical method obtained the seeing value in daily variation of Albireo (β Cyg) star trail with surface meteorological as a predictor parameter. The standard error of estimate (S-Value) between predictor parameter (pressure and humidity) with Albireo star seeing are reached 0.0027543 in two days variation. Based on the result, the three Membership Functions (MFs) with Gaussian function was proposed in this study to develop FIS trail of star. The result shows that the configuration analysis from input parameter FIS with 15 role bases from surface meteorological parameter has successful to targeted with Albireo (β Cyg) star trail. The 15 role bases from FIS was used to estimate seeing value from meteorological parameter in near future.